2017
DOI: 10.1104/pp.17.00110
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Induced Remodeling of the Photosynthetic Machinery Tunes Photosynthesis in the Thermophilic Alga Cyanidioschyzon merolae

Abstract: The thermophilic alga thrives in extreme environments (low pH and temperature between 40°C and 56°C). In this study, we investigated the acclimation process of the alga to a colder temperature (25°C). A long-term cell growth experiment revealed an extensive remodeling of the photosynthetic apparatus in the first 250 h of acclimation, which was followed by cell growth to an even higher density than the control (grown at 42°C) cell density. Once the cells were shifted to the lower temperature, the proteins of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 58 publications
3
12
0
Order By: Relevance
“…1D), from which a near atomic x-ray structure was obtained (Jordan et al, 2001). The wide temperature tolerance of isolated C. merolae PSII (Krupnik et al, 2013) and PSI-LHCI complexes (this study) is most likely the reason for the remarkable wide temperature range tolerance of this extremophilic alga, as shown in a recent study (Nikolova et al, 2017).…”
Section: Biochemical and Proteomic Characterization Of The C Merolaesupporting
confidence: 63%
“…1D), from which a near atomic x-ray structure was obtained (Jordan et al, 2001). The wide temperature tolerance of isolated C. merolae PSII (Krupnik et al, 2013) and PSI-LHCI complexes (this study) is most likely the reason for the remarkable wide temperature range tolerance of this extremophilic alga, as shown in a recent study (Nikolova et al, 2017).…”
Section: Biochemical and Proteomic Characterization Of The C Merolaesupporting
confidence: 63%
“…3 c, d). Similar, temperature-dependent activity of C. merolae was observed before (Nikolova et al 2017 ). The mutant cells were more susceptible to temperature than the WT and a drop of the ambient temperature to 25 °C has diminished the activity of both mutants by ~ 50% while the WT retained as much as ~ 65% of its activity from 37 °C conditions.…”
Section: Resultssupporting
confidence: 88%
“…A similar increase in the growth rate was also observed in the photoautotrophic sister lineage of Cyanidioschyzon , where cultures of Cyanidioschyzon merolae 10D were grown at 25°C for a period of ∼100 days, albeit under photoautotrophic conditions. This study found that the cold-adapted cultures outgrew the control culture at the end of the experiment (Nikolova et al, 2017). While faster doubling times at 28°C can be attributed to gradual adaptation to the suboptimal growth temperatures, we may only speculate about the causes leading to slower growth in the control condition (42°C).…”
Section: Discussionmentioning
confidence: 87%
“…Variants affecting the genetic code of genes attributed to this category influence a broad variety of metabolic pathways (e.g., “cellular aromatic compound metabolic process,” GO:0006725, p = 0.0030 and “amine metabolic process,” GO:0009308, p < 0.0001) in both anabolism (e.g., “peptidoglycan biosynthetic process,” GO:0009252, p = 0.0015 and “glycerol biosynthetic process,” GO:0006114, p = 0.0086), and catabolism (e.g., “glycosaminoglycan catabolic process,” GO:0006027, p = 0.0011). In spite of pronounced changes in gene expression of metabolic enzymes during short-term cold stress in G. sulphuraria 074W (Rossoni et al, 2018) and Cyanidioschyzon merolae 10D (Nikolova et al, 2017), microevolution of genes directly involved in metabolic steps appeared to play a minor role in long-term temperature adaptation (34/234 GOs, 14.5%).…”
Section: Resultsmentioning
confidence: 99%